Core–shell shaped Ni2CoHCF@PPy microspheres from prussian blue analogues for high performance asymmetric supercapacitors. (13th August 2021) - Wu, Shang; Feng, Qiaoliang; Zhou, Sheng; Zhao, Huanlei; Xu, Xin; Su, Qiong; Wang, Yanbin; Sun, Yuzhi; Yang, Quanlu
Abstract: Recently, prussian blue analogues (PBAs), as the most classical class of metal-organic frameworks, have been widely studied by scientists. Nevertheless, the inferior conductivity of PBAs restricts the application in supercapacitors. In this work, nickel cobalt hexacyanoferrate (Ni2 CoHCF) had been produced via a simple co-precipitation approach and coated with polypyrrole on its surface. The conductivity of PBAs was improved by the polypyrrole coating. The Ni2 CoHCF@PPy-400 microspheres were demonstrated to the outstanding specific capacity of 82 mAh g −1 at 1 A g −1 . After 3000 cycles, the Ni2 CoHCF@PPy-400 microspheres had a long cycle life and 86% specific capacity retention rate at 5 A g −1 . Additionally, it was coupled with activated carbon to build high performance asymmetric supercapacitor (Ni2 CoHCF@PPy-400//AC), which displayed a high energy density of 21.7 Wh kg −1 at the power density of 888 W kg −1 and good cycle stability after 5000 cycles (a capacity retention rate of 85.2%). What is more, the results reveal that the Ni2 CoHCF@PPy-400 microspheresare a prospective candidate for exceptional energy storage devices.